2017
DOI: 10.3168/jds.2016-11928
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo fruit extract as an additive to modify rumen microbiota and fermentation and to mitigate methane production

Abstract: Ginkgo fruit, an unused byproduct of the ginkgo nut industry, contains antimicrobial compounds known as anacardic acids. Two major cultivars of ginkgo, Kyuju (K) and Tokuro (T), were evaluated for their potential as a feed additive for ruminants. In batch culture, we incubated a mixture of hay and concentrate in diluted rumen fluid with or without 1.6% (fruit equivalent) ginkgo fruit extract. We conducted another series of batch culture studies to determine the dose response of fermentation. We also conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 46 publications
7
63
0
Order By: Relevance
“…This may be the reason for the least methane reduction with the 1:9 ratio (14.6%, Table 2). A previous study (Oh et al 2017) reported that ammonia was decreased by ginkgo extract in the artificial rumen, possibly by inhibiting hyper-ammonia producing bacteria such as Peptostreptcoccus anaerobious, Clostridium aminophilum, Clostridium sticklandii (Chen & Russell 1989). The effect of dietary ginkgo extract supplementation on rumen ammonia was not clear (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This may be the reason for the least methane reduction with the 1:9 ratio (14.6%, Table 2). A previous study (Oh et al 2017) reported that ammonia was decreased by ginkgo extract in the artificial rumen, possibly by inhibiting hyper-ammonia producing bacteria such as Peptostreptcoccus anaerobious, Clostridium aminophilum, Clostridium sticklandii (Chen & Russell 1989). The effect of dietary ginkgo extract supplementation on rumen ammonia was not clear (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…higher propionate and lower methane production) as a result of microbial selection (Oh et al 2017). higher propionate and lower methane production) as a result of microbial selection (Oh et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations